A giant ancient schwannoma mimicking an adnexal mass: Case report. Issue 30 (July 2016) - Karaköse, Oktay; Pülat, Hüseyin; Oğuz, Serhat; Zihni, İsmail; Özçelik, Kazım Çağlar; Yalta, Tülin Deniz; Eken, Hüseyin
Abstract: Introduction: Ancient schwannoma is a rare tumor of the peripheral nerve sheath. As degenerative properties are defined histologically, it can be wrongly interpreted as malignant. Case presentation: The case presented here is of a giant ancient schwannoma with a pelvic retroperitoneal location, which was mimicking an adnexal mass. Conclusion: In the rarely seen cases in the retroperitoneum, it may reach very large dimensions.